INTRODUCTION TO LIQUID ORGANIC FERTILIZER FROM SOURSOP LEAF EXTRACT AT MADRASAH IBTIDAIYAH NEGERI 5 IN BANDA ACEH CITY: PENGENALAN PUPUK ORGANIK CAIR DARI EKSTRAK DAUN SIRSAK DI MADRASAH IBTIDAIYAH NEGERI 5 KOTA BANDA ACEH - Mizar Liyanda; Maghfirah, Maghfirah; Chairil Anwar; Sri Agustina; Ika Rezvani Aprita; Endiyani; Irhami; Mulyanti; Kurnia; Humeira; Zulvia Maika Letis; Hatipah (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Liquid organic fertilizer offers numerous benefits, including enhancing soil fertility, promoting plant growth, and reducing the need for chemical fertilizers that can have a negative environmental impact. The Community Service Program (PKM) aims to provide information to students of Madrasah Ibtidaiyah Negeri 5 Kota Banda Aceh on the production and use of soursop leaf extract as a liquid organic fertilizer, as well as new knowledge for students on how to utilize natural resources in their surroundings to improve the school's economic environment. Fertilization through leaves has another advantage: nutrients are more quickly absorbed by plants through the stomata of the leaves, resulting in visible new growth, such as new shoots. The students of Madrasah Ibtidaiyah Negeri 5 Banda Aceh were very enthusiastic and interested in processing liquid organic fertilizer with soursop leaf extract, thereby expanding the community's knowledge and increasing the students' understanding of using soursop leaf POC as a material for making natural fertilizer.